Social Organization and Musical Style in the Court Music of the Alaafin of Oyo - Ajewole, John Olugbenga (2015)
This study examined the court music of the Alaafm of Oyo in order to establish its origin, development, organization, and performance. This was with a view to highlighting the aesthetic and moral functions embedded in the music.